Species differentiation by internally transcribed spacer PCR and HhaI digestion of fluconazole-resistant Candida krusei, Candida inconspicua, and Candida norvegensis strains. - Nho, S (1997)
PCR amplification of the regions containing the internally transcribed spacers and 5.8S rRNA gene of Candida krusei, C. inconspicua, and C. norvegensis yielded fragments of 510, 460, and 500 bp, respectively. HhaI digestion of these fragments yielded species-specific bands. Random amplification of polymorphic DNA with primer R108 showed interspecific discriminatory band patterns. Susceptibilities to fluconazole and amphotericin B were determined.